THE CONCEPT OF UTILITARIANISM IN THE SHORT STORY “THE ONES WHO WALK AWAY FROM OMELAS” IN “THE WIND'S TWELVE QUARTERS” BY URSULA KROEBER LE GUIN - Siti Nurrohmah Azizah; Mahi M. Hikmat (Universitas Negeri Surabaya, 2023)
This study examines the concept of utilitarianism presented in the short story